2023
DOI: 10.3390/diagnostics14010083
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy and Dissection of the Hypogastric Plexus in Nerve-Sparing Radical Hysterectomy

Stoyan Kostov,
Yavor Kornovski,
Angel Yordanov
et al.

Abstract: Radical hysterectomy is a central surgical procedure in gynecological oncology. A nerve-sparing approach is essential to minimize complications from iatrogenic injury to the pelvic nerves, resulting in postoperative urinary, anorectal, and sexual dysfunction. The hypogastric plexus (HP), a complex network of sympathetic and parasympathetic nerves, plays a critical role in pelvic autonomic innervation. This article offers a comprehensive overview of the surgical anatomy of the HP and provides a step-by-step des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
(240 reference statements)
0
7
0
Order By: Relevance
“…The course of vesical branches of the IHP has been described as consistent with two terminal branches by Mauroy et al [5,18], matching our findings. These branches have been shown to travel with the ureter as it approaches the bladder in a recent anatomical study describing nervesparing radical hysterectomy methods (see Figure 16 of [10]; the vesical branches of the IHP are termed "bladder nerve branches" in that study). Another study has also reported that the vesical branches join the last segment of the ureter at the base of the bladder along its lateral border (see Figure 5 in [9]).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The course of vesical branches of the IHP has been described as consistent with two terminal branches by Mauroy et al [5,18], matching our findings. These branches have been shown to travel with the ureter as it approaches the bladder in a recent anatomical study describing nervesparing radical hysterectomy methods (see Figure 16 of [10]; the vesical branches of the IHP are termed "bladder nerve branches" in that study). Another study has also reported that the vesical branches join the last segment of the ureter at the base of the bladder along its lateral border (see Figure 5 in [9]).…”
Section: Discussionmentioning
confidence: 99%
“…These parasympathetic pelvic splanchnic nerves join inferior branches of the hypogastric nerves to form the inferior hypogastric plexus (IHP, also termed the pelvic plexus [4]), located on both the right and left sides of the pelvis [5][6][7][8]. Sympathetic sacral splanchnic nerves from sacral located sympathetic ganglia also send branches into the IHP [9][10][11]. The anterior division of the IHP supplies nerve fibers to the bladder and ureter (i.e., vesical branches of the IHP, also known as vesical branches of the pelvic nerve [12][13][14][15][16], anterior branches of the IHP [9,17,18], and bladder nerve branches [10]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations